Aplicação da análise de jarabak, no estudo da relação entre a altura total facial anterior e posterior, em pacientes portadores de má-oclusão de classe I e classe II divisão 1 de angle, por meio de radiografias cefalométricas - Becker, João Batista Macedo [UNESP] (1998)
ln order to predict the facial growth using Jarahak's analysis, cephalometric radiographies of 120 subjects during the mixed dentition and between 6 and 10 years of age were studied. From the total, 60 subjects (30 males and 30 females) were classified as Angle's Class I and 60 subjects (30 males and 30 females) were classified as Angle's Class II, Division 1. AIl subjects did not receive any orthodontic treatment. The proportion between anterior and posterior facial heigth (SGo-NMe) was studied, which is determined by the formula PFH x 100/ AFH = %, neither being straight (> 62% < 65), clockwise ( > 58% < 62%) and anti-clockwise ( > 65% - 80%). Mean average, standard deviation and facial height proportion (SGo - NMe) were determined for males and females according to Angle's classification of malocc!usion. Sexual dimorphism was examined with regard to different types of Angle's malocclusion and the direction of the facial growth, and the correlation of four cephalometrics measurements were analvsed